Reciprocity and gift exchange in markets for credence goods - Kandul, Serhiy; Lanz, Bruno; Reins, Evert (My University, 2023)
We study the role of reciprocity in markets where expert-sellers have more information about the severity of a problem faced by a consumer. We employ a standard experimental credence goods market to introduce the possibility for consumers to gift the expert-seller before the diagnostic, where the gift is either transferred unconditionally or conditionally on solving the problem. We find that both types of gifts increase the frequency of consumer-friendly actions relative to no gift, but only conditional gifts translate into efficiency gains when the consumer faces a high-severity problem. This suggests that partial alignment of incentives via conditional gifts may outweigh kindness motives when reciprocal actions are not directly observed. Using further treatments with surprise gift exchange, we show that withholding a gift that is expected by expert-sellers significantly reduces the likelihood of consumer-friendly behavior whereas sending a gift to expertsellers who do not expect one has no effect.